Compact CPW-fed triple-band MIMO antenna for wireless body area network based on flexible liquid crystal polymer. Issue 10 (3rd July 2022) - Du, Chengzhu; Liu, Hongye; Wang, Xun; Nie, Yu; Yang, Zhipeng
Abstract : A compact coplanar waveguide-fed triple-band multiple input multiple output (MIMO) antenna is designed based on flexible substrate named liquid crystal polymer in this work. The proposed antenna comprises two antenna elements placed side by side. By adding a double Y-shaped branch between two antenna elements, good isolation is achieved successfully, which is better than 21 dB. According to the measured results, it can operate bandwidth covering 2.263–2.925, 3.063–4.5 and 4.588–7.25 GHz, meeting the radio spectrum, including 5G, WLAN and WiMAX. Moreover, the proposed antenna also has virous suitable characteristics including envelope correlation coefficient (<0.01), diversity gain (>9.99), channel capacity loss (<0.4 bits/s/Hz), the difference of mean effective gain (<0.15 dB) and total active reflection coefficient (<−10 dB). The bending test and the effect of human body have also been analyzed. The actual measurement indicates that the presented MIMO antenna is desirable for integration in wearable 5G/WLAN/WiMAX devices.